(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The utilization of workmanship structures is as yet broad all through the world. Hollow concrete blocks have supplanted customary bricks in late development as a result of the upsides of higher bearing limit, farmland insurance, and energy protection [1]. The hollow concrete blocks, being lightweight result in a reduced dead load of the structure [2]. They are practical and a superior option in contrast to consumed dirt blocks by their great solidness, imperviousness to fire, have good thermal protection, less dead burden, and high speed of development [3]. They are economical in comparison to the existing building materials. This project includes the preparation of samples of hollow concrete blocks with the different number of cavities and different shapes of cavities (circular and rectangular) using a concrete mix of 1:4:6 and a comparative study is executed concerning brick masonry and the blocks available in the market. The strength parameter, economy, lightweight character, and insulation property are studied and compared. The compressive qualities of the samples are thought about after permitting them to solution for 28 days in the curing tank. The thermal insulation test, block density test, and water absorption test are also carried out. The results showed a great deal of insulation from temperature. The energy consumption of buildings can be reduced to a significant amount by using these blocks [6]. The compressive parameters of these samples came to be far more than those of blocks that are being utilized in the market. Therefore these types of hollow concrete blocks can prove to revolutionize the way we design and build our structures.